The Macaque Connection Cooperation and Conflict between Humans and Macaques - Radhakrishna, Sindhu; Huffman, Michael A.; Sinha, Anindya (Developments in Primatology: Progress and Prospects,, 2013)
Most successful among the non-human primates in terms of geographical distribution and adaptability to ecological habitats, macaques have existed for many thousands of years in close contact with modern humans, the only primate more successful than them. Centuries-old literary works attest to the fact that macaques have always been an intrinsic part of human lives and imaginations. In their interactions with humans, macaques play multiple roles that often transcend the boundaries of categorization. They are often, simultaneously, wildlife and domestic pets, sentient beings and experimental subjects, crop-raiding pests and religious symbols.  In many parts of the tropics, macaques are an economic resource for human communities, as they provide meat and money through tourism and the animal trade. Equally, they cause much damage and bring about great economic losses due to their crop- and house-raiding tendencies. A more recent cause for alarm has been the possibility of transmission of diseases to humans due to contact with macaques. Across Asia, macaques, perhaps more than any other animal species, exemplify the multiple facets of synurbization and the conservation problems of commensal species.   Humans and macaques associate in rather remarkable ways, and this volume explores the tone and nature of those human-macaque connections by focusing on various forms of interactions between macaques and humans, change in human attitudes vis-à-vis macaques over the ages, cultural views on macaques, human-macaque conflict and its conservation implications. Its holistic perspective of the myriad aspects that illustrate the singular relationship between men and macaques makes it essential reading not only for primatologists and anthropologists but also for anyone interested in the intricacies of human-animal relations.